INCREASED RATE OF ACETYLCHOLINESTERASE SYNTHESIS IN DIFFERENTIATING NEUROBLASTOMA CELLS - Lanks, Karl W. (The Rockefeller University Press, 1974)
When neuroblastoma cells (N18) in vitro are maintained in the absence of serum, the specific activity of AChE begins to rise rapidly after an initial lag period of about 2–3 days, reaching a maximum level (10–20-fold increase) by 7 days after induction. In order to clarify the mechanism of induction, it was necessary to measure the rate of AChE synthesis and its sensitivity to metabolic inhibitors. Return of enzymatic activity after irreversible inhibition of AChE in "differentiated" cells was blocked by cycloheximide, but not by cordycepin or actinomycin D, suggesting that protein but not mRNA synthesis was required for replacement. By using the initial rate of this replacement as a measure of the rate of synthesis of the enzyme, it was shown that cells which had differentiated in the absence of serum synthesized AChE 50-fold faster on a specific activity basis than their undifferentiated counterparts. In contrast, cordycepin effectively blocked the increase in the rate of AChE synthesis that occurs as a result of serum deprivation, indicating that the induction process itself requires the synthesis of new mRNA. Axonation, another index of differentiation, was not completely blocked by inhibition of RNA or protein synthesis and presumably utilizes only pools of pre-existing structural proteins.